1992
DOI: 10.1115/1.2929009
|View full text |Cite
|
Sign up to set email alerts
|

Transformation Plasticity and Residual Stresses in Single-Pass Repair Welds

Abstract: Prediction of the residual stresses caused by welding is important when post-weld stress relief is not feasible. Phase changes and transformation plasticity have a significant effect on the residual stresses generated by welding and heat-treatment of some alloys. Transformation plasticity occurs when the stresses generated by the transformation of individual grains interact with the macroscopic stress state to produce plastic strains. Heuristic methods requiring empirical constants have been used in the past. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 0 publications
0
13
2
Order By: Relevance
“…11,12,[62][63][64][65][66][67] Nevertheless, attempts to include the effect of solid-state phase transformation on volumetric strain and yield strength of weld material in modelling residual stresses are reported in recent studies. [68][69][70][71][72][73][74][75][76][77][78] Taljat et al…”
Section: Introductionmentioning
confidence: 99%
“…11,12,[62][63][64][65][66][67] Nevertheless, attempts to include the effect of solid-state phase transformation on volumetric strain and yield strength of weld material in modelling residual stresses are reported in recent studies. [68][69][70][71][72][73][74][75][76][77][78] Taljat et al…”
Section: Introductionmentioning
confidence: 99%
“…A combined kinematic/isotropic model may more accurately represent the material behaviour however, for simplicity, and considering only a single weld pass is made in this model, isotropic behaviour has been assumed. The material's microstructural evolution is likely to be a more significant effect than the hardening behaviour, however reasonable residual stress and distortion predictions can usually be found without directly modelling such complexities [3,26]. The annealing temperature used was 850 °C which corresponds to the ferritic-austenitic phase transformation temperature.…”
Section: Thermal-mechanical Materials Properties and Conditionsmentioning
confidence: 99%
“…Finite element models for welding have been developed over many years [1][2][3]; good predictions for residual stresses can routinely be obtained in materials where transformation plasticity is not a concern and where the heat source has been correctly calibrated. However, distortion predictions have proved more difficult, although for idealised situations where restraint is not a concern good predictions can also be obtained, providing that appropriate element types are used [4].…”
Section: Introductionmentioning
confidence: 99%
“…Oddy et al [1] have shown the significance of transformation strain on the final predicted residual stress field in single-pass repair welds. The mechanisms for generating have been found to be dependent on both the deviatoric stress state present during SSPT, as well as the transformation rate [6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have highlighted the importance of solid-state phase transformation (SSPT) kinetics in the analysis of ferritic steel weld models [1][2][3]. The total strain is influenced by a reversible volumetric strain ( ) due to changes in crystal structure during SSPT, and also by a finite irreversible transformation strain ( ).…”
Section: Introductionmentioning
confidence: 99%